RNA-Seq Revealed a Circular RNA-microRNA-mRNA Regulatory Network in Hantaan Virus Infection - Lu, Shuang; Zhu, Ni; Guo, Weiwei; Wang, Xin; Li, Kaiji; Yan, Jie; Jiang, Cuiping; Han, Shiyu; Xiang, Hanmin; Wu, Xiaohan; Liu, Yuanyuan; Xiong, Hairong; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Hantaan virus (HTNV), a Hantavirus serotype that is prevalent in Asia, causes hemorrhagic fever with renal syndrome (HFRS) with high mortality in human race. However, the pathogenesis of HTNV infection remains elusive. Circular RNAs (circRNAs), a new type of non-coding RNAs, play a crucial role in various pathogenic processes. Nevertheless, circRNA expression profiles and their effects on pathogenesis of HTNV infection are still completely unknown. In the present study, RNA sequencing was performed to analyze the circRNA, microRNA (miRNA), and mRNA expression profiles in HTNV-infected and mock-infected human umbilical vein endothelial cells (HUVECs). A total of 70 circRNAs, 66 miRNAs, and 788 mRNAs were differently expressed. Several differentially expressed RNAs were validated by RT-qPCR. Moreover, we verified that some differentially expressed RNAs, such as circ_0000479, miR-149-5p, miR-330-5p, miR-411-3p, RIG-I, CMPK2, PARP10 and GBP1, promoted or inhibited HTNV replication. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis demonstrated that the host genes of differentially expressed circRNAs were principally involved in the innate immune response, the type I interferon (IFN) signaling pathway, and the cytokine-mediated signaling pathway. Additionally, the circRNA-miRNA-mRNA regulatory network was integrally analyzed. The data showed that there were many circRNA-miRNA-mRNA interactions in HTNV infection. By dual-luciferase reporter assay, we confirmed that circ_0000479 indirectly regulated RIG-I expression by sponging miR-149-5p, hampering viral replication. This study for the first time presents a comprehensive overview of circRNAs induced by HTNV and reveals that a network of enriched circRNAs and circRNA-associated competitive endogenous RNAs (ceRNAs) is involved in the regulation of HTNV infection, thus offering new insight into the mechanisms underlying HTNV-host interaction.